Analisis Perhitungan Penyusutan Aset Tetap terhadap Laba Perusahaan PT. Campina Ice Cream Industry Tbk - Bayti Jannati; Widya Astuti Alam Sur; Ines Saraswati Machfiroh (Indonesian Journal of Applied Accounting and Finance, 2021)
This study focuses on the calculation of depreciation of fixed assets on profit using 3 methods, namely the straight-line method, the number of years method, and the double-declining balance method. The purpose of this research is to find out which depreciation method has the most influence on the company's profit and to find out whether the company's choice has been effective or not. Based on the calculation results, it is known that depreciation using the straight-line method is more dominant and has a positive impact on the company's profit PT.Campina Ice Cream Industry Tbk. While the use of the number of years method and the double-declining balance method is less effective for companies because of the uneven treatment of charges and decreases every year so that at the beginning of the accounting period the profits obtained tend to be small, while in the next period until the end of the life of the fixed assets, the profits obtained high value